SENSITIZATION AND CORROSION IN AISI 316L (Journal of Industrial and Mechanical Engineering, 2025)
This work studies the accelerated corrosion of AISI 316L stainless steel under exposure to a saline atmosphere for 96h. The samples were previously solution-treated at 1100°C for 1 hour and then cooled in water or air, followed by isothermal sensitization at 650°C for 6 hours. Microstructural analysis, using optical and scanning electron microscopy, revealed severe attacks at the austenitic grain boundaries, attributed to the precipitation of different types of chromium carbides and intermetallic phases, as confirmed by X-ray diffraction. Corrosion tests indicated that the air-cooled sample exhibited a higher degradation rate and mass loss, with significant advancement of intergranular corrosion, compared to the water-cooled one. These findings highlight the influence of heat treatments on susceptibility to localized corrosion.
Keywords: Intergranular Corrosion; Heat Treatments